CONFIRMATION OF ALTAI-MONGOLIA MICROCONTINENT AND ITS IMPLICATIONS - Li H.J.; He G.Q.; Wu T.R.; Wu B. (My University, 2006)
Chinese Altai has proterozoic basement, and probably experienced four major events during Proterozoic era. Research about Precambrian basement is the base of dertermination of Altai-Momgolia microcontinent. The span of Habahe group extending about 1500 kilometers is from Sinian to Middle Ordovician and is belived to be continental margin sediment of Altai-Mongolia microtinent. Research about Habahe group is the key to determine Altai-Mongolia microtinent. Dongxileke group formed during the relaxing stage after two continent (Altai-Mongolia and Siberia) collided, Baihaba granite formed during post-collional tectonic environment. Research about Dongxileke group and Baihaba granite is important evidence of determining Altai-Momgolia microcontinent. The northern and southern edges of Altai-Momgolia microcontinent are ascertained. Altai-Mongolia microcontinent is a immature continent mainly composed of proterozoic matter according to geochemical data of Habahe group.
Keywords: ALTAI; BASEMENT; HABAHE GROUP; MICROCONTINENT; Докембрий::Протерозой; Палеозой::Ордовикская; Палеозой::Кембрийская; Precambrian::Proterozoic; Paleozoic::Ordovician; Paleozoic::Cambrian